PERAKITAN CHASSIS DAN POWERTRAIN KENDARAAN URBAN CONCEPT HEMAT ENERGI UNTUK KONTES MOBIL HEMAT ENERGI DI SMK N 1 SAMBI - Ellyawan Setyo Arbintarso; Aji Pranoto; Bambang Wahyu Sidharta; Imam Taqorub (Jurnal PkM Pemberdayaan Masyarakat, 2022)
The Energy Efficient Car Contest - Kontes Mobil Hemat Energi (KMHE) is an annual national level fuel efficient car competition organized by the National Achievement Center - Pusat Prestasi Nasional (Pusprenas) of the Indonesian Ministry of Education, Culture, Research and Technology in collaboration with one of the universities in Indonesia as the host. One of the categories of competition in KMHE is the Urban Concept type, which is a four-wheeled vehicle that looks like a car in general and is suitable for driving on the road with an internal combustion motor driven with alcohol as an alternative fuel. Vehicle weight is a major obstacle in efforts to save fuel. Vehicles must be designed in such a way that they are light in weight but without compromising their ability to drive. The weight of the Urban Concept vehicle is contributed by the engine, powertrain, body, chassis and driver's weight. The engine used must use an engine on the market (using premium/pertalite/pertamax fuel), so that weight reduction can only be done in other components. On this occasion, the students of SMK Negeri 1 Sambi, Boyolali, Central Java were given the concept of how to design a chassis and powertrain that meets the needs of a vehicle but is light in weight.